Kebijakan Ekonomi Politik Indonesia dan Tanggapan Masyarakat di Desa Panti Sumatera Barat - Fifi Febriandiela; Yulhendri; Lince Magriasti (Jurnal Ekonomi Aktual, 2023)
The purpose of the study topic called political economy is to look at political and economic forces interacting in a society. Political economists see the relationship between politics and the economy as an interconnected system in which economic structure can influence political policy and vice versa. The growth and history of political economy began in the 18th century with the introduction of economic theories by philosophers and economists such as Adam Smith and David Ricardo. They developed economic ideas, which are considered the cornerstones of contemporary economic growth. Incorporating aspects of socialism, nationalism and monotheism, the Indonesian Pancasila serves as a unifier for all existing ideas in Indonesian society. The study of political economy combines two different fields of study, politics and economics. Both must, coordinate human activities, handle conflicts, distribute costs and rewards, and satisfy human needs and wants. They must also show the same concern for organizational difficulties. In addition, handling the pandemic from an economic and political perspective is a challenge for the government and is a crucial issue. The implementation of these policies has its own difficulties because careful consideration must be given so that they can be carried out properly and efficiently. Qualitative research and descriptive techniques were used in this study. The findings of this study indicate that political economy policies in Indonesia have succeeded in gaining support from residents of Panti Village, Panti District, and Pasaman District. Indeed, there are still certain challenges, but the parties participating in this assistance program can overcome them.